Prevalence and risk factors for epilepsy in children with spastic cerebral palsy - Dedy Rahmat; Irawan Mangunatmadja; Bambang Tridjaja; Taralan Tambunan; Rulina Suradi (Paediatrica Indonesiana, 2010)
Background Epilepsy in cerebral palsy (CP) is usually difficult to treat and can lead to poor prognosis due to increased risk for motor and cognitive disorders. The prevalence and risk factors of epilepsy in children with CP vary among studies.Objective To determine the prevalence and risk factors for epilepsy in spastic CP.Methods We performed a retrospective study using medical records of patients with spastic CP at the Departement of Child Health, Cipto Mangunkusumo Hospital from January 2003 until December 2008. Prevalence ratio was calculated by comparing the prevalence of epilepsy in subjects with and without risk factors. We excluded patients with metabolic disorder, genetic syndrome, and onset of CP after 3 years of age.Results Two hundred thirty six out of 238 spastic CP patients were analyzed. The mean age at diagnosis of spastic CP was 28.8 months. Male to female ratio was 1.4:1. The prevalence of epilepsy in spastic CP was 39%. The risk factors for epilepsy in spastic CP were central nervous system infection, the ocurrence of seizure in the first year of life, and abnormality of EE G.Conclusions The prevalence of epilepsy in spastic CP is 39%. The risk factors for epilepsy in spastic CP are post central nervous system infection, and ocurrence of seizure in the first year of life. [Paediatr Indones. 2010;50:11-7].